Dynamic tests of the culvert face within crashtests - Luboš Nouzovský; Tomáš Kohout; Pavel Vrtal; Jakub Nováček (Acta Polytechnica CTU Proceedings, 2022)
Severity of a vehicle impact into solid obstacles alongside  the road can be annually illustrated through accident statistics. One example of such solid obstacles is drainage ditch culvert faces. Within the research at the Faculty of Transportation Sciences of the Czech Technical University new equipment has been designed in a form of a modular system of the drainage ditch culvert faces construction. The qualities of this equipment have been tested by means of crash tests with a passenger vehicle Škoda Fabia making use of criteria of biomechanical endurance of the vehicle passengers. The results have been compared with the test carried out by means of a vehicle crash into concrete culvert faces.